Assessing REALTER simulator: analysis of ocular movements in simulated low-vision conditions with extended reality technology - Barbieri, Mattia; Albanese, Giulia A.; Merello, Andrea; Crepaldi, Marco; Setti, Walter; Gori, Monica; Canessa, Andrea; Sabatini, Silvio P.; Facchini, Valentina; Sandini, Giulio (Frontiers in Bioengineering and Biotechnology, 2024)
Immersive technology, such as extended reality, holds promise as a tool for educating ophthalmologists about the effects of low vision and for enhancing visual rehabilitation protocols. However, immersive simulators have not been evaluated for their ability to induce changes in the oculomotor system, which is crucial for understanding the visual experiences of visually impaired individuals. This study aimed to assess the REALTER (Wearable Egocentric Altered Reality Simulator) system’s capacity to induce specific alterations in healthy individuals’ oculomotor systems under simulated low-vision conditions. We examined task performance, eye movements, and head movements in healthy participants across various simulated scenarios. Our findings suggest that REALTER can effectively elicit behaviors in healthy individuals resembling those observed in individuals with low vision. Participants with simulated binocular maculopathy demonstrated unstable fixations and a high frequency of wide saccades. Individuals with simulated homonymous hemianopsia showed a tendency to maintain a fixed head position while executing wide saccades to survey their surroundings. Simulation of tubular vision resulted in a significant reduction in saccade amplitudes. REALTER holds promise as both a training tool for ophthalmologists and a research instrument for studying low vision conditions. The simulator has the potential to enhance ophthalmologists’ comprehension of the limitations imposed by visual disabilities, thereby facilitating the development of new rehabilitation protocols.